Optimalisasi Pembakaran Waste Oil pada Pesawat Incinerator di kapal MT. PIS Polaris - Sanjaya, Aglika; Mustholiq; Yuntoro, Kresno (Indonesian Journal of Marine Engineering, 2024)
Waste oil or dirty oil is oil that comes from operational processes of machinery on board. The aim of this research is to find out what impacts are caused by optimizing the burning of waste oil in the operation of incinerator on ships in terms of marine pollution, as well as to find out efforts to optimize the burning of waste oil in incinerator aircraft on MT. PIS Polaris. The research method used by the author in this research is a qualitative method. Research data sources were obtained from primary data and secondary data. Data collection techniques use observation, literature study, documentation and interviews, data validity techniques use triangulation techniques. The data analysis technique used by researchers in this research is the Shell method (Software, Hardware, Environment and Liveware). The results of research on the impact of optimizing the burning of waste oil on incinerator are complying with international Marine Pollution regulations which regulate the prevention of pollution at sea, apart from that it also prevents pollution of the marine environment as a result of illegal disposal of waste oil and also the disposal of rubbish from ships that will endangering the life of ecosystems at sea level and ecosystems under the sea. Then it can also extend the life of the incinerator components by implementing PMS (Plan Maintenance System) and checking procedures in accordance with the instructions in the manual book. Then the research results from efforts to optimize the burning of waste oil in incinerator are by carrying out PMS (Plan Maintenance System) and regular maintenance routines as well as carrying out maintenance on each component of the incinerator and complying with operating procedures according to the instructions in the manual book, then selecting the appropriate waste elements. will be burned and the engine crew must understand the contents of the manual book which is used as a reference or guideline in dealing with any problems that occur at the incinerator. Waste oil atau minyak kotor merupakan limbah minyak yang berasal dari proses operasional permesinan yang ada di dalam kapal. Tujuan penelitian ini adalah untuk mengetahui Untuk mengetahui dampak apa saja yang ditimbulkan dengan mengoptimalkan pembakaran waste oil pada pengoperasian pesawat incinerator di atas kapal dalam hal pencemaran laut, serta untuk mengetahui upaya optimalisasi pembakaran waste oil pada pesawat incinerator di kapal MT. PIS Polaris. Metode penelitian yang digunakan penulis pada penelitian ini adalah metode kualitatif. Sumber data penelitian diperoleh dari data primer dan data sekunder. Teknik pengumpulan data melalui observasi, studi pustaka, dokumentasi, dan wawancara, teknik keabsahan data menggunakan teknik triangulasi. Teknik analisis data yang digunakan peneliti dalam penelitian ini adalah metode Shell (Software, Hardware, Environment, dan Liveware). Hasil penelitian dari dampak optimalisasi pembakaran waste oil pada pesawat incinerator yakni mematuhi regulasi international Marine Pollution yang mengatur tentang pencegahan pencemaran di laut, selain itu juga mencegah terjadinya pencemaran lingkungan laut akibat dari tindakan pembuangan waste oil secara illegal dan juga pembuangan sampah dari atas kapal yang akan membahayakan kehidupan ekosistem di permukaan laut, ekosistem yang ada di bawah laut. Kemudian juga dapat memperpanjang usia komponen incinerator karena menerapkan PMS (Plan Maintenance System) dan prosedur pengecekan sesuai dengan petunjuk yang ada pada manual book. Kemudian hasil penelitian dari upaya optimalisasi pembakaran waste oil pada pesawat incinerator yakni dengan cara melaksanakan PMS (Plan Maintenance System) dan routine maintenance secara teratur serta melakukan perawatan pada tiap komponen incinerator dan mematuhi prosedur pengoperasian sesuai petunjuk pada manual book, kemudian melakukan pemilihan unsur sampah yang akan dibakar dan engine crew harus memahami isi dari manual book yang digunakan sebagai acuan atau pedoman dalam menangani setiap masalah yang terjadi pada incinerator.